Percutaneous endoscopic gastrostomy: results of 115 cases - (:unkn) unknown (My University, 2003)
BACKGROUND/AIMS: Percutaneous endoscopic gastrostomy is one of the gastrostomy methods used for patients who are unable to take food orally. We aimed to present our results for percutaneous endoscopic gastrostomy. METHODOLOGY: One hundred and fifteen patients undergoing percutaneous endoscopic gastrostomy by pull technique were retrospectively evaluated in terms of indications, complications, durability of tube, and mortality. RESULTS: Of the 115 cases, 60 were males and 55 females with the median age of 67 (2-93) years. Indications for percutaneous endoscopic gastrostomy placement were cerebrovascular accident in 39, brain tumors in 24, subarachnoidal hemorrhage in 21, several neurologic disorders in 17, miscellaneous extracerebral tumors in 6, head injury in 5, hypoxic encephalopathy in 2, and iatrogenic in 1. The durability of the tube was a median of 242 (9-1988) days. The tube was removed in 16 patients and was changed in 11 patients with a median interval of 142.5 (35-427) and 133 (24-1251) days, respectively. Four wound infections, two buried bumper syndromes, and two aspiration pneumonias developed. Total follow-up was 114.1 patient-years with procedure-related mortality, 30-day mortality, and overall mortality of 0%, 3.5% (4/115), and 17.4% (20/115), respectively. The mortality rate was 45% for patients who had brain tumor and 11.6% for the remainder. CONCLUSIONS: Percutaneous endoscopic gastrostomy is a minimally invasive gastrostomy method with low morbidity and mortality rates, easy to follow-up, and easy to replace when clogged.
Keywords: Adult; Female; Humans; Middle Aged; Postoperative Complications; Aged; Aged, 80 and over; Adolescent; Male; Follow-Up Studies; Child; Retrospective Studies; Child, Preschool; Equipment Failure; Surgical Wound Infection; Brain Diseases; Survival Rate; Device Removal; Neuromuscular Diseases; Enteral Nutrition; Gastrostomy; Gastroscopy